Economic assessment of an integrated waste to energy system for an urban sewage treatment plant: A numerical approach. (1st September 2018) - Montorsi, L.; Milani, M.; Venturelli, M.
Abstract: The economic assessment of an integrated anaerobic digestion and gasification system for the exploitation of the residues from an urban sewage treatment plant is carried out. The obtained bio-fuels are used in a cogeneration unit to produce both electric and thermal energy. The analysis focuses on the water treatment plant of a touristic town, characterized by a highly variable number of inhabitants. Therefore, the amount of input biomass for the integrated plant results remarkably time dependent and the design accounts for the transient nature of the input. The performance of the integrated system is modelled by developing an ad-hoc dynamic library for the simulation of the energy conversion systems under the OpenModelica open source platform. The system's performance and economic assessment are modelled by means of equations and correlations that calculate the components' behaviour on a time dependent basis. The simulation demonstrates that the final wastes to landfill decrease by a 73% improving significantly the environmental impact of the plant. Furthermore, the proposed integrated system is able to produce the 25% of the electric energy required for the plant operation. Thus, the payback period of the integrated plant results to be lower than 3 years. Highlights: Transient numerical modelling of combined waste to energy technologies is developed. The energy recovery from an urban sewage treatment plant is predicted. The 25% of electric energy required for the total plant operation is produced. The 73% reduction of final residues to landfill is calculated. Plant's economic analysis is determined and payback period is less than 3 years.